Value of alpha smooth muscle actin (αSMA) and inducible nitric oxide synthase (iNOS) in oral squamous cell carcinoma (OSCC): An immunohistochemical approach to tumor stroma categorization and clinicopathological parameters - Heba E.M. Youssef; Basant Hamdy AbouZaid (Oral Oncology Reports)
Objectives: The aggressive behavior of oral squamous cell carcinoma (OSCC) is not only a cancer-cell centered issue, but also affected by tumor stroma. Cancer-associated fibroblasts (CAFs) are the most abundant component of tumor stroma that can direct tumorigenesis. Alpha smooth muscle actin (α-SMA) expression by stromal CAFs is linked to higher aggressive tumor behavior and poor prognosis. Inducible nitric oxide synthase (iNOS) is one of the main enzymes producing the free radical, nitric oxide in response to various stimuli. Its increased expression revealed several pro-tumorigenic effects. This study was undertaken to address the expression of α-SMA and iNOS in OSCC in relation to tumor stroma type and degree of tumor cell differentiation. Methodology: Thirty-two archival specimens of OSCC were stained immunohistochemically with anti-α-SMA and anti-iNOS. Stromal categorization was performed according to the ratio between α-SMA positive areas and the density of tumor infiltrating lymphocytes. The immunohistochemical score of iNOS was evaluated semi-quantitatively. Finally, correlations between stroma category, iNOS expression and different clinicopathological parameters were performed. Results: Our results revealed a significant positive correlation between advanced histopathologic grade and the higher stromal category (P = 0.02). Additionally, increased stroma category was significantly associated with advanced clinical stage (P = 0.001) and nodal involvement (P = 0.05). Likewise, iNOS expression was significantly correlated with worsened histopathological grade (P = 0.008) and clinical stage of tumors (P = 0.01). Conclusions: Combining the assessment of stroma category and iNOS expression offers a more comprehensive tumor microenvironment profile in OSCC, surpassing single-parameter approaches focused solely on tumor or stromal characteristics.